PERANAN KEBIJAKAN FISKAL DALAM SEBUAH NEGARA - Desi Isnaini (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
Fiscal policy is an important component of public policy. Public policy is a tool to achieve the welfare of human life. Fiscal policy is the adjustment in the income and expenditure of government asset out in the budget revenue and expenditure is shortened state budget to achieve the desired economic stability is generally setin the development plan. In Islam fiscal policy include the material and spiritual well-being based on moral values.The roleof fiscal policyin general is for the allocation of natura lresources, the distribution of income and economic stability, but in Islam there are differences in fiscal commitments with three additional roles that establish economic equality, forbids the paymentof interestand help the local economy is less developed. Policies can be done with development accompanied by justice and stability.